ACUTE HYPOKALEMIC PARALYSIS AND HASHIMOTO’S THYROIDITIS - Ullah, Rafiq; Naeem, Awais; Naim, Fahad; Zia, Qasim; Hamayun, Omama (Journal of Ayub Medical College Abbottabad, 2022)
Acute hypokalemic paralysis (AHP) is a life-threatening emergency. It is exceptionally unusual for hypothyroidism to present with AHP. This association can be either primary or secondary through distal renal tubular acidosis. We report two cases who presented with acute quadriplegia. The succeeding investigations revealed severe hypokalemia and autoimmune hypothyroidism. The second case was found to have Sjogren’s syndrome additionally. The underlying etiology of hypokalemia in both cases was found to be dRTA. The combination of such conditions is reported sporadically. Here we also discuss the potential association of AHP with autoimmune conditions by proxy through dRTA.